2004
DOI: 10.4049/jimmunol.173.4.2236
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Differential Roles for Phosphoinositide 3-Kinases, p110γ and p110δ, in Lymphocyte Chemotaxis and Homing

Abstract: Despite the established role for PI3Ks in cell migration, the PI3Ks involved in lymphocyte chemotaxis are poorly defined. In this study, we report that p110γ-deficient T cells, but not B cells, show reduced chemotactic responses to the lymphoid chemokines, CCL19, CCL21, and CXCL12. As B cell and T cell chemotactic responses were both sensitive to the general PI3K inhibitors, wortmannin (WMN) and LY294002, we explored whether B cell responses were affected in mice lacking p110δ, a major PI3K isoform in lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
191
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(221 citation statements)
references
References 18 publications
27
191
2
Order By: Relevance
“…WT and p110␦ D910A/D910A T cells populated peripheral lymph nodes with similar efficiencies (Fig. 4A, day 0 time point), consistent with a nonessential role for p110␦ in T cell migration (31). In response to immunization with OVA in combination with LPS, clonal expansion of p110␦ D910A/D910A T cells was severely reduced in comparison with WT cells (Fig.…”
Section: P110␦ Controls Clonal T Cell Expansion In Vivosupporting
confidence: 53%
“…WT and p110␦ D910A/D910A T cells populated peripheral lymph nodes with similar efficiencies (Fig. 4A, day 0 time point), consistent with a nonessential role for p110␦ in T cell migration (31). In response to immunization with OVA in combination with LPS, clonal expansion of p110␦ D910A/D910A T cells was severely reduced in comparison with WT cells (Fig.…”
Section: P110␦ Controls Clonal T Cell Expansion In Vivosupporting
confidence: 53%
“…In normal lymphocytes, optimal polarization and migration in response to CCL19, CCL21 or CXCL12 is dependent on the expression of DOCK2, a Rac GTPase exchange factor, and PI3K. Whereas in T cells PI3K-dependent migration is mainly mediated by PI3Kγ, in B cells class IA PI3K is required for their efficient chemotaxis and homing to LNs (7,8).…”
Section: Ccl19 and Ccl21 Increase B-cll Cells Survivalmentioning
confidence: 99%
“…Class I PI3Ks are heterodimeric molecules composed by a regulatory and a catalytic subunit that generate phosphatidylinositol-3,4,5-triphosphate (PIP3), which have a key role in cell migration (6). Class I PI3Ks are further subdivided into class IA and class IB isoforms, which are involved in the chemotaxis and homing of B and T lymphocytes, respectively (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the difference between B and T cells, B cells require DOCK2 for integrin activation, while T cells do not [8]. A recent study indicated that WMN treatment impaired the entrance of mouse B cells into Peyer's patches and the splenic white pulp, but did not statistically reduce entrance into the inguinal and mesenteric lymph nodes [9]. Following firm adhesion to HEV, lymphocytes transmigrate through the endothelium and enter the parenchyma of lymph nodes or Peyer's patches.…”
Section: Introductionmentioning
confidence: 99%